Loading...

3k-1=k+2 2k=3 k=3/2=1.5

When factored it is: (3k+5)(k-1)

The question is unclear, so the author will provide answers for a number of interpretations: 1. 3k-6(2k+1) = 3k-12k-6=-9k-6=-3(3k+2) 2. 3k-6(2k)+1=3k-12k+1=-9k+1 3. (3k-6)(2k)+1 = 6k^2 -12k + 1 = 6(k-1-sqrt(5/6))(k-1+sqrt(5/6)) 4. (3k-6)(2k+1) = 6k^2 - 12k + 3k - 6 = 6k^2 -9k + 6 = 3(2k^2 - 3k + 2) Line 4 cannot be factorised further. sqrt and ^2 refer to the square root, and squared respectively. Lines 1 and 2 require knowledge of expansion of linear equations, addition of like terms, and factorisation of linear equations. Lines 3 and 4 also require knowledge of addition of like terms, and expansion and factorisation of quadratic equations. In no case can an exact value for k be determined as we were given an expression rather than an equality.

2k - 1 = 0 Add 1 to both sides: 2k = 1 Divide both sides by two: k = 0.5

It is the associative property of addition in the sense that a sum of three elements is unambiguous even if given without brackets to indicate which of the sums is carried out first. This would not apply for subtraction since 1 - (3k - 6) = 1 - 3k + 6 whereas (1 - 3k) - 6 = 1 - 3k - 6

K+1 is as simplified as it gets. Unless you find the value of K. You can't add a variable and number.

Is the following what you are claiming? 2k = 2k+1 -1 20 not equal 20+1 - 1 21 not equal 21+1 -1

2k + 5

Let even be of the form 2k and odd be of the form 2k+1. Then odd * even becomes 2k*2k+1, or 4k^2 +2k. This can be written as 2(k^2 + k), which is of the form 2k. Therefore, odd X even equals even.

No...it equals 4...

4+1=5. Plus 4 equals 9. Plus 77685769844446473 equals 77685769844446482. Plus 3 equals 77685769844446485. Plus 8 equals 77685769844446493. Plus 1 equals 77685769844446494. Plus 9870998342523322424 equals 1064785604097768918. Plus 4 equals 1064785604097768922.

no if 1 plus 1 equals 2 then 2 plus 2 equals 4.

1 plus 1 plus 1 plus 1 equals 1 times 4. 1 times 4 equals 4. 4 minus 4 equals 0. 0

To prove that 2k 2k plus 1-1 by induction is a step by step process. But the induction 2 is not equal to 2 to the power of 0 take away 1.

You can prove that 2K,2K,1-1 by first determining that the integer N can be written in the form of N=2K.

2048

1 plus 1 equals 1 (in Boolean logic) 1 plus 1 equals 10 (in base 2)

3 plus 1 plus 4 equals 8

1 plus 1 equals one fact

This appears to be a number trick or joke. The answer is that 1 hour, plus 1 minute, plus 59 minutes, will equal 2 hours.

Equation: 2kx^2 -2x^2 +2kx +k -1 = 0 Using the discriminant: (2k)^2 -4*(2k -2)*(k -1) = 0 Solving for k in the discriminant: k = 2 + or - square root of 2

6+1 equals 7. Plus 3 equals 10. Plus 4 equals 14.

No it equals 2 10 plus 1 equals 11

20

6-2kx=5-2x 2x-2kx=-1 x(2-2k)=-1 x=-1/(2-2k)